COVID-19 Pandemic and Digitalization of Service Organizations: A Trademark Approach. - Alan, Hale (Electronic Turkish Studies, 2020)
The Coronavirus (COVID-19) pandemic, which deeply affects almost all countries around the world, has unprecedented effects on businesses and industries so far. During the ongoing COVID-19 pandemic, there was a greater need for the use of internet technologies and digital applications.Due to the necessity of using digital technology-based applications to meet these needs, all countries have focused on digitalization today and have given more importance. Innovations using various advanced technologies are needed to overcome the various problems associated with this viral pandemic.Innovation allows firms to create unique products or services from competitors aiming to create value for customers. In this respect, digital technologies greatly change the evolution of product or service innovation. In the last 10 years, the effects of digital transformation on services and service innovations are rarely predictable.The aim of this study isto reveal the reflections of the digitalization effect and digital transformation on service innovations during the COVID-19pandemic. This researches focus on digital service mark applications in the pandemic. It is possible to determine the digitalization tendency through the classes in the service mark application dataset. For this, digital service innovations are classified according to the international nice classification system. In this study, service mark applications are used as a dataset to analyze the digitalization effect on services.Analysis of service marks may contribute to a better understanding of innovation in services. As a result, it is seen that the areas most affected in the service sector are related to business management services such as human resources applications,and e-commerce platforms that aim to serve customers. In addition, it has been revealed that the digitalization tendency is high, especially in the health, education and tourism sectors.